2023
DOI: 10.1002/gdj3.177
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of symmetry index in minerals

Abstract: Crystal structures of minerals are defined by a specific atomic arrangement within the unit‐cell, which follows the laws of symmetry specific to each crystal system. The causes for a mineral to crystallize in a given crystal system have been the subject of many studies showing their dependency on different formation conditions, such as the presence of aqueous fluids, biotic activity and many others. Different attempts have been made to quantify and interpret the information that we can gather from studying cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(41 reference statements)
1
9
0
Order By: Relevance
“… Hystad and colleagues [ 38 ] have demonstrated that more than 3000 additional mineral species on Earth exist, but have yet to be discovered and described. New mineral species are being discovered at a rate of approximately 100 species per year [ 39 ], and many of those display complex, previously unknown structures [ 34 , 40 ]. …”
Section: Discussionmentioning
confidence: 99%
“… Hystad and colleagues [ 38 ] have demonstrated that more than 3000 additional mineral species on Earth exist, but have yet to be discovered and described. New mineral species are being discovered at a rate of approximately 100 species per year [ 39 ], and many of those display complex, previously unknown structures [ 34 , 40 ]. …”
Section: Discussionmentioning
confidence: 99%
“…An additional constraint arises from the mobility of chemical elements in depth of Earth where no partial melts occur and where only metasomatosis through supercritical fluids acts as a potential means of mobilizing and segregating less common elements [23]. Moreover, chemically bonded water augments the number of potential mineral species in general [11,24]. maining high Z data that are not silicates are phosphate-, arsenate-, borate-, or molybdate framework structures.…”
Section: Statistical Distribution Of Structuresmentioning
confidence: 99%
“…In the effort to develop a more accurate metric of symmetry through time, in this paper, we did not only use the maximum multiplicities of holohedral classes of each crystal system but rather the maximum multiplicities of all 32 point groups. This approach resulted in a formula similar to the one given by Bermanec et al [30]:…”
Section: Introductionmentioning
confidence: 95%
“…Starting with the pioneering work of Naumann [3], who investigated the distribution of 546 mineral species within crystal systems, several researchers have considered the world of mineral symmetry from a statistical standpoint [4][5][6][7][8][9][10]. Bermanec and colleagues [11] investigated symmetry distributions among 5674 International Mineralogical Association Minerals 2024, 14, 387 2 of 11 (IMA)-approved minerals species as of October 2022 from https://rruff.info/ima (accessed on 5 March 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation